Community Empowerment through Traditional Snack Production and Marketing Training to Increase Family Income - M. Imron Mas'ud; Ayik Pusakaningwati; Nuriyanto; Moh. Muhyidin Agus Wibowo; Abdul Wahid; Subchan Asy’ari; Abdul Ghofar (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community empowerment program aimed to enhance the entrepreneurial capacity of women through traditional snack production and marketing training in Sladi Village, Kejayan District, Pasuruan Regency, Indonesia. The program involved 30 members of the Family Welfare Empowerment (PKK) group and adopted a participatory approach consisting of preparation, training implementation, and evaluation stages. The training covered healthy traditional snack production, food hygiene and sanitation, production cost calculation, and digital marketing strategies. The results indicated improvements in participants’ knowledge and practical skills related to food production, financial management, and online promotion. Evaluation findings showed a high level of participant satisfaction, with 100% of participants expressing satisfaction with the training facilities, facilitator performance, usefulness of activities, product quality outcomes, and willingness to participate in similar programs in the future. Furthermore, participants demonstrated increased entrepreneurial motivation and greater confidence in developing home-based businesses. The program highlights the effectiveness of integrating technical, financial, and marketing competencies to support women’s empowerment, improve family income opportunities, and promote sustainable community development.